ENTREPRENEURIAL EMPOWERMENT IN CREATING SUSTAINABLE DEVELOPMENT IN DEVELOPING COUNTRIES: TO WHAT EXTENT DO THEY STRENGTHEN AND CONTRIBUTE TO EACH OTHER? - Nazhira Nindya Padma Hanuun; M. Rizqi Padma Negara; Zaenal Aripin (Journal of Jabar Economic Society Networking Forum, 2023)
Entrepreneurial empowerment's role in fostering sustainable development in developing countries is a critical and intriguing topic. This journal aims to explore the extent of their mutual reinforcement and contribution. Conducted in the form of a literature review, this research utilizes a qualitative method, comprehensively examining various sources to provide a nuanced understanding. Findings indicate a positive correlation between entrepreneurial empowerment and sustainable development in developing countries. Entrepreneurial empowerment provides individuals with opportunities to develop their skills and innovations, aligning with the goals of sustainable development, including sustainable economic growth, environmental preservation, and social welfare. In conclusion, this study suggests that entrepreneurial empowerment can be a key factor in creating sustainable development in developing countries. Recommendations are provided to enhance entrepreneurial empowerment, with the aim of achieving more effective sustainable development goals. This journal covers relevant references, including books, scholarly journals, articles, and other pertinent documents, within the last five years. Thus, the journal contributes a better understanding of the significance of entrepreneurial empowerment in driving sustainable development in developing countries and its contribution to economic growth and societal welfare.